Current mode voltage reference - Goh, Siow Chnia (2015)
The report proposed a bandgap voltage reference circuit design to generate a low voltage reference which is independent to variations temperature, process and noise by using higher order compensation in current mode approach. The experiment on the characterization and the temperature behaviour of the BJT transistor used was done and investigated and the model was effectively developed in the circuit designed under Chartered Semiconductor Manufacturing (CSM) 0.18um n-well CMOS process. The operational amplifier was designed to have a high output swing and high gain. The proposed bandgap voltage reference circuit is able to work properly under a supply voltage down to 1V. The temperature coefficient of the circuit is 5.91ppm/℃ over a wide range of temperature of -40℃ to 125℃. The power consumption is 356.976uW , the line regulation of the circuit designed was 45.2uV/V and the PSRR of the circuit is 77.23dB under normal operating condition in 300K. The operational amplifier has a relatively high gain of 79.16dB and the phase margin is around 83.82 deg. The unity bandwidth (f_T) is around 2.855MHz. All the circuit simulation is performed by using Cadence program provided by school.